Vrste ustava tradicionalne kineske medicine i apolipoprotein B u hiperurikemiji: Udruženja sa kardiovaskularnim rizikom Tradicionalna kineska medicina Ustav Tipovi i Apolipoprotein B u hiperurikemiji: Udruženja sa kardiovaskularnim rizikom: TCM Types and Apo B in Hyperuricemia - Yang, Shuo; Li, Jinfeng; Zeng, Hongli; Zhang, Xueping; Xiong, Deliang; Tang, Wenyi; Sun, Bin; Yu, Peng; He, Xiaohong; Zhang, Weizheng (Journal of Medical Biochemistry, 2025)
Background: To explore the correlation between different traditional Chinese medicine (TCM) constitution types and apolipoprotein B (ApoB) in patients with hyperuricemia (HUA), and to investigate the relationships between TCM constitutions, uric acid levels, and various cardiovascular risk factors.Methods: A cross-sectional study involving 683 patients diagnosed with HUA was conducted. Patients' TCM constitutions were classified using the standardized "Classification and Determination of TCM Constitution" questionnaire. Serum uric acid (UA), lipid profiles, ApoB, and homocysteine (Hcy) levels were measured. Results: Among 683 HUA patients, phlegm-dampness (22.99%) and damp-heat constitution (20.06%) were the most common TCM constitution types. UA, ApoB, and Hcy levels in patients with phlegm-damp constitution were significantly higher than those in other constitutions (P